WES-2-Absorbing Submodules and WEQ-2-Absorbing Submodules - Wissam A. Hussein; Haibat K. Mohammad Ali (Tikrit Journal of Pure Science)
In this research, we introduced and studied, the concepts of WES-2-absorbing submodules and WEQ-2-absorbing submodules as a stronger form of the concepts of weakly semi-2-absorbing submodules and weakly quasi-2-absorbing submodules respectively, and give their basic properties, examples and characterizations. On the otherhand, we studied the relationships among these concepts. Furthermore, we studied the behavior of these concepts in some classes of modules.